Ileostomy Complications in Infants less than 1500 grams – Frequent but Manageable - Kargl, Simon; Wagner, Oliver; Pumberger, Wolfgang (Journal of Neonatal Surgery, 2016)
Background: In very low birth weight infants abdominal emergency surgery may result in ileostomy formation. We observed a frequent stoma complications in these patients. This retrospective analysis put light on ileostomy-related problems and complications in very low birth weight (VLBW) infants. Materials and Methods: In a seven-year retrospective chart review (2008 - 2014) infants with ileostomy formation weighing less than 1500 grams at time of operation were identified and reviewed. Data analysis included demographic data, complications and short term outcomes. Results: Thirty patients were included. Ileostomy was formed for spontaneous intestinal perforation (SIP) (n=17), meconium obstruction of prematurity (MOP) (n=6), midgut volvulus (MV) (n=5), necrotizing enterocolitis (NEC) (n=1) and Hirschsprung’s disease (HD) (n=1). Three patients died before ileostomy reversal was considered. In seven patients planned ileostomy reversal was done. Twenty infants had stoma related complications (stoma prolapse, prestomal obstruction, stoma retraction, high output stoma, peristomal skin excoriation, and stomal ischemia). Complications did not correlate with underlying diseases. Stomal complications necessitated earlier stoma reversal (mean 62 days). Postoperative complications after stoma reversal occurred in three children (wound dehiscence, adhesion ileus, anastomotic stricture). Conclusions: Although ileostomy related complications are frequent in very low birth weight infants, mortality is low. Morbidity is manageable.